Table of Content - - (Journal of Educational and Psychological Sciences, 2025)
Table of Content: 1. The Role of female principals of school in Enhancing Information Security at the Secondary Level in Al-Kharj Governorate Ms. Suha Fahad Al-Mosa 2. Proposed Research priorities for Doctoral dissertations in educational administration at Taibah University and the Islamic University in Al-Madinah Ms. Maha Saleh Saad Alyahyan , Ms. Wafiah Othman Alsubhi ,Co-Prof. Norah Mohamed Aljumah 3. Employing modern technology to support the teaching and learning process in primary schools in Al-Dakhiliyah Governorate in the Sultanate of Oman Dr. Ali Saif Al-Durai 4. Psychological stress and its relationship life Satisfaction among a sample of male and female students at Taif University Ms. Amjad Ahmed Alzahrani ,Dr. Suha Omar Alharthi 5. The Effect of the Parental Treatment Style of the Firm Mother on Social Adjustment in University Life Among Students of Sultan Qaboos University in the Sultanate of Oman Ms. Farida Said Sulaiman Alsharji,Co-Prof. Norwati Mansour 6. Relationship of Bullying with psychological security and Self-Esteem among a sample of first year students at Tabuk University in Tabuk Ms. Joud Masad Alodhayyani, Dr. Ahmed Ali Alhomidi 7. Evaluating the Implementation of the Training Needs Assessment Policy at Imam Muhammad ibn Saud Islamic University Dr. Dalia Abdulaziz Alharbi, Dr. Alaa Ibrahim Alhijji, Dr. Manal Trekhem Alharthi , Co-Prof. AlJawhrah Othman Ali AlRakban